2022
DOI: 10.3390/jof8060560
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative and Cytotoxic Cytochalasins from Sparticola triseptata Inhibit Actin Polymerization and Aggregation

Abstract: Laying the groundwork on preliminary structure–activity relationship study relating to the disruptive activity of cytochalasan derivatives on mammalian cell actin cytoskeleton, we furthered our study on the cytochalasans of the Dothideomycetes fungus, Sparticola triseptata. A new cytochalasan analog triseptatin (1), along with the previously described cytochalasans deoxaphomin B (2) and cytochalasin B (3), and polyketide derivatives cis-4-hydroxy-6-deoxyscytalone (4) and 6-hydroxymellein (5) were isolated from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…USCF Chimera (version 1.13.1) was used to facilitate the removal of bound residues and minimization of structures. Dock-prepping of ligand and protein structures was done using Antechamber, and molecular docking was performed using the BFGS algorithm of AutoDock Vina (version 1.1.2) . Validation of the docking protocol was done via the redocking experiment of the co-crystallized ligands.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…USCF Chimera (version 1.13.1) was used to facilitate the removal of bound residues and minimization of structures. Dock-prepping of ligand and protein structures was done using Antechamber, and molecular docking was performed using the BFGS algorithm of AutoDock Vina (version 1.1.2) . Validation of the docking protocol was done via the redocking experiment of the co-crystallized ligands.…”
Section: Methodsmentioning
confidence: 99%
“…Dock-prepping of ligand and protein structures was done using Antechamber, and molecular docking was performed using the BFGS algorithm of AutoDock Vina (version 1.1.2). 23 Validation of the docking protocol was done via the redocking experiment of the co-crystallized ligands. The conformational protein–ligand structure was visualized and analyzed using Biovia Discovery Studios (version 4.1).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, following treatment with ChA ( 4 ), ChB ( 5 ), chaetoglobosin D (ChD, 61 ), ChJ ( 54 ), ChA monoacetate ( 60 ), and ChD diacetate ( 62 ), it was observed that cells are not able to spread again during a washout on the substratum after rounding, which was then shown to constitute a concentration-dependent effect. We encountered a similar phenomenon and attempted to estimate treatment conditions inferred from the extent of F-actin-disrupting effects [ 76 , 77 , 78 , 79 ]. Doing this, we observed that indeed there is a subset of compounds that tend to induce longer-lasting effects on F-actin networks, whereas other cytochalasans are again readily reversible.…”
Section: Correlating Cytochalasan Chemodiversity With the Activity Sp...mentioning
confidence: 99%
“…Doing this, we observed that indeed there is a subset of compounds that tend to induce longer-lasting effects on F-actin networks, whereas other cytochalasans are again readily reversible. The physicochemical reasons for this behavior are unclear, but they seem to be linked to the modification of the macrocycle, which will be elaborated upon in a later passage [ 76 , 77 , 78 , 79 ].…”
Section: Correlating Cytochalasan Chemodiversity With the Activity Sp...mentioning
confidence: 99%
“…In all cases, solvent effects have been included by employing the polarizable continuum model (PCM), which is often used in the ECD calculations. 47,50,51 Based on the excitation energies and rotational strengths obtained from TD-DFT, the theoretical ECD spectra were generated using the program Multiwfn. 52 2.2.2 QM/CSM calculations.…”
Section: Determination Of the Rc And Bamentioning
confidence: 99%